Effect of Different Fungicides and Phytoextracts on Growth Inhibition of Alternaria burnsii - Pipliwal, S.K.; Jadeja, K.B.; Sharma, Anshul (Annals of Agricultural Research, 2017)
An experiment was conducted on cumin crop and the treatment set of fungicides and phytoextractswere tested for their inhibitory effect on spore germination of Alternaria burnsii causing cumin blightwas performed in in vitro condition. In the laboratory screening systemic fungicides, hexaconazole,propiconazole, tebuconazole and non systemic fungicides, mancozeb executed 100 per cent growthinhibition of A. burnsii, the cumin blight pathogen. Among the phytoextracts tested against A. burnsiiunder in vitro conditions, Turmeric rhizome (70.55%), garlic clove (67.45 %) and ginger rhizome(62.79 %) at 10 per cent proved most effective phytoextracts for growth inhibition of A. burnsii.